2013
DOI: 10.1259/bjr.20120433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adaptive radiotherapy techniques for the treatment of bladder cancer

Abstract: Objective: Day-to-day anatomical variations complicate bladder cancer radiotherapy treatment. This work quantifies the impact on target coverage and irradiated normal tissue volume for different adaptive strategies. Methods: 20 patients were retrospectively planned using different three-dimensional conformal radiotherapy treatment strategies for whole-bladder carcinoma: (i) ''conventional'' treatment used isotropic expansion of the clinical target volume (CTV) by 15 mm to the planning target volume (PTV) for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 14 publications
0
48
0
7
Order By: Relevance
“…In addition to one in silico implementation of online compensation [58], these were the only studies where feedback from delivered dose triggered adaptations. Contributing to differences in applied strategies and workflows could be the additional manual contouring, which was a pre-requisite in over 70% of the simulated ART workflows [22,59,60,[62][63][64][65][66][68][69][70]72,74,78,79,[81][82][83]85,86,88,89,91,93,[95][96][97][98][100][101][102][103][104][105][106][107]. To reduce the need of manual contours, the segmentation could be propagated using deformable image registration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to one in silico implementation of online compensation [58], these were the only studies where feedback from delivered dose triggered adaptations. Contributing to differences in applied strategies and workflows could be the additional manual contouring, which was a pre-requisite in over 70% of the simulated ART workflows [22,59,60,[62][63][64][65][66][68][69][70]72,74,78,79,[81][82][83]85,86,88,89,91,93,[95][96][97][98][100][101][102][103][104][105][106][107]. To reduce the need of manual contours, the segmentation could be propagated using deformable image registration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous treatment planning studies have compared different techniques to create PTVs in adaptive plan selection radiotherapy [5,18]. This study is the first to compare two clinically implemented ART strategies for bladder cancer directly, using both TCP modeling and calculation of normal tissue parameters from EQD2 distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that adaptive radiotherapy (ART) may reduce normal tissue dose by selecting an optimal plan from a patient-specific plan library, according to daily patient anatomy [3][4][5][6][7]. Several plan selection strategies have been proposed, all of which are based on creating multiple treatment plans prior to or during treatment, by imaging multiple anatomical variations [3][4][5][6][7]. For every treatment fraction, the plan best fitting the daily bladder volume as assessed on cone beam computed tomography (CBCT) is selected.…”
mentioning
confidence: 99%
See 2 more Smart Citations